Development of 'EduGame Mathematics' Gamification-Based Application to Enhance Learning Interest of Elementary School Students in 3T Regions - Muhajir, Muhajir; Afandi, Ahmad; Husain, Husriani; Sappaile, Baso Intang; Karmila, Mila (PT Inovasi Pratama Internasional, 2025)
Background: The digital divide in Indonesia's underdeveloped, frontier, and outermost (3T) regions creates significant challenges for mathematics education in elementary schools. Traditional teaching methods often fail to engage students, resulting in low learning motivation and poor academic outcomes. Objective: This study aims to develop and evaluate the effectiveness of 'EduGame Mathematics,' a gamification-based mobile learning application designed to enhance learning interest among elementary school students in 3T regions. Methods: A quantitative experimental research design was employed using a pretest-posttest control group design. The study involved 120 elementary school students (grades 4-6) from three schools in 3T regions, randomly assigned to experimental (n=60) and control (n=60) groups. Data collection instruments included learning motivation questionnaires, mathematics achievement tests, and application usability assessments. Statistical analysis was conducted using independent t-tests and paired t-tests with SPSS 25.0. Results: The experimental group demonstrated significantly higher learning motivation scores compared to the control group (M=85.4, SD=8.2 vs M=68.7, SD=9.1; t(118)=10.45, p<0.001). Mathematics achievement scores showed substantial improvement in the experimental group, with a mean increase of 24.3 points (from 62.1 to 86.4), while the control group showed minimal improvement of 5.2 points (from 61.8 to 67.0). The application received high usability ratings (M=4.31/5.0) and demonstrated strong acceptance among students and teachers. Conclusion: The EduGame Mathematics application effectively enhances learning interest and achievement among elementary school students in 3T regions. The gamification approach successfully addresses educational challenges in resource-constrained environments, providing a scalable solution for improving mathematics education quality in remote areas of Indonesia.